2021
DOI: 10.1007/s13399-020-01250-7
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient adsorptive membrane for heavy metal removal based on Ulva fasciata biomass

Abstract: New composite adsorptive membranes were prepared from non-living Ulva fasciata (U), marine algae and cellulose acetate (CA) as polymer matrix to develop CA-U composite membranes with different ratios using the phase inversion technique. These CA-U membranes were used for cadmium (Cd 2+ ) and zinc (Zn 2+ ) ion removal from aqueous media. The prepared membranes were characterized via different instrumental techniques as ATR-FTIR, SEM and EDX in addition to swelling and porosity measurements. Afterwards, they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…[5,7,8] Because of the drawbacks of most of these methods, namely, high cost of operation, residual waste generation, limited processing capacity, and complicated procedure, their uses have become limited. [2,9,10] Comparatively, it has been found that the adsorption process is one of the best methods used for water treatment. This is because this method is distinguished by its simple design, cost-effectiveness, easy operation and handling, good efficiency, and the availability of a wide range of adsorbent materials.…”
Section: Introductionmentioning
confidence: 99%
“…[5,7,8] Because of the drawbacks of most of these methods, namely, high cost of operation, residual waste generation, limited processing capacity, and complicated procedure, their uses have become limited. [2,9,10] Comparatively, it has been found that the adsorption process is one of the best methods used for water treatment. This is because this method is distinguished by its simple design, cost-effectiveness, easy operation and handling, good efficiency, and the availability of a wide range of adsorbent materials.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of algae Fucus vesiculosus with biosorbents such as calcium alginate polyethylenimine showed higher selectivity for Pb and Cu over Cd, Zn, and Ni (Demey et al, 2018). Composites of nonliving Ulva fasciata (U) with cellulose acetate-based polymeric membranes were found to be effective for Cd 2+ and Zn 2+ from aqueous solutions (Abdelhamid et al, 2021). The high specificity and doubling in the uptake of Cu from even aqueous solutions was achieved by the use of magnetized derivatives of biochar of waste macroalgae kelp, with magnetization aiding an additional advantage of easy separation of heavy metals (Son et al, 2018).…”
Section: Algaementioning
confidence: 99%
“…Biopolymers as chitosane and nanochitosane and their composites were used as a prominent adsorbent for heavy metals and CR removal [22][23][24][25][26][27][28][29][30]. Different nanomaterials and nanocomposites have been used in a variety of science applications such as biomedical and environmental, especially as dye's adsorbants [31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%